Water calcium concentration modifies whole-body calcium uptake in sea bream larvae during short-term adaptation to altered salinities - Guerreiro, P. M. (2014)
Whole-body calcium uptake was studied in gilthead sea bream larvae (9–83·mg) in response to changing environmental salinity and [Ca2+]. Calcium uptake increased with increased fish size and salinity. Fish exposed to calcium-enriched, diluted seawater showed increased calcium uptake compared with fish in diluted seawater alone. Calcium uptake was unchanged in Na+- enriched, diluted seawater. Overall, [Ca2+], and not salinity/osmolarity per se, appears to be the main factor contributing to calcium uptake. By contrast, drinking was reduced by a decrease in salinity/osmolarity but was little affected by external [Ca2+]. Calculations of the maximum contribution from drinking-associated calcium uptake showed that it became almost insignificant (less than 10%) through a strong decrease in drinking rate at low salinities (0–8‰). Diluted seawater enriched in calcium to the concentration present in full-strength seawater (i.e. constant calcium, decreasing salinity) restored intestinal calcium uptake to normal. Extra-intestinal calcium uptake also benefited from calcium addition but to a lesser extent.